A dual‐polarized end‐fire mmWave antenna array without ground clearance for 5G mobile terminals. Issue 5 (13th February 2021) - Yue, Zhenzhen; Liu, Ying; Zhao, Chang; Ren, Aidi; Chen, Yuenian; Jia, Yongtao; Xu, Yunxue; Ye, Mao
Abstract: A broadband dual‐polarized end‐fire millimeter‐wave antenna array without ground clearance is proposed in this paper for 5G communication terminals. Horizontally polarized (HP) and vertically polarized (VP) radiation are realized using a quasi‐Yagi antenna and a substrate‐integrated waveguide cavity antenna, respectively. A multilayer dielectric plate for which the relative dielectric constant increases from top to bottom is used to achieve the HP antenna's end‐fire radiation without ground clearance. The VP antenna is implemented using the HP antenna, GND, and three rows of metallic vias. The HP and VP antennas are located in the same area, making the integrated design very compact. An inverted L‐shaped feeding structure was used to broaden the VP antenna's bandwidth with a low profile (0.12 λ L ). Finally, a 4 × 1 array was processed to verify the proposed antenna. The measured results show that the overlapping bandwidth is 24 to 29.5 GHz (20.6%) for two polarization modes. The maximum gain varies between 7.6 to 9.1 and 6.5 to 9.1 dBi for the HP and VP modes, respectively.